Macy finished a job in 3/4 hours . James finished it in 4/5 of the time Macy took. How Long did James take to finish the job?

Answers

Answer 1
Answer: 3/4 hours is equal to (60 minutes divided by 4) times three. [15*3 = 45] 
Macy finished in 45 minutes. Now we have to find 4/5 of 45. So (45 divided by 5) times 4. [9*4 = 36] 
See the pattern? So the answer for 45 minutes divided by 4/5 is 36 minutes.
Answer 2
Answer: 36 minutes is the correct answer

Related Questions

2(x +8) what would that be ?
Write a related subtraction fact for 5+7=12
4 mi 1,389 yd - 4 mi 251 yd =
What is 6.46,6.41 and 4.6 in order from least to greatest
Solve the equation 4 1/5+b= 9 3/5 b=---and if you could work it out and show me that would help a lot.

Solve w + 1⁄4 < 7⁄8.

Answers

Answer:

w <0.125

Step-by-step explanation:

Answer:

w < 5/8

Step-by-step explanation:

Aim to isolate w.  Subtract 1/4 from both sides, obtaining:

w < 7/8 - 2/8 (since the LCD here is 8)

Then:

w < 5/8

Find the distance between the points (6, 5 square root 2) and (4, 3square root 2).

Answers

For this case we use the distance formula between two points.

We have then:

d=√((x2-x1)^2+(y2-y1)^2)

Substituting values in the given equation we have:

d=\sqrt{(6-4)^2+(5√(2)-3√(2))^2}

Rewriting the equation we have:

d=\sqrt{(2)^2+(2√(2))^2}

d=√(4+8)

d=√(12)

d=√(3*4)

d=2√(3)

Answer:

The distance between the points is:

d=2√(3)

The distance would be 2√3 , in other words it is 2 square root 3

What's 12p+5pd-3p+6pd

Answers

12p+5pd-3p+6pd\n\nUse\ commutative\ property:a+b=b+a\nand\ associative\ property:(a+b)+c=a+(b+c)\n\n=(12p-3p)+(5pd+6pd)=\huge\boxed{9p+11pd}

12p+5pd−3p+6pd

=12p+5dp+−3p+6dp

Combine Like Terms:

=12p+5dp+−3p+6dp

=(5dp+6dp)+(12p+−3p)

=11dp+9p


Solve the system of linear equations below.

y = -2x + 19
y = x + 7

Answers

Hey there!

y = -2x + 19
y = x + 7

We gonna solve this system of equation by using the substitution method.

We wanna solve y = -2x + 19 for y

Let start by substitute -2x + 19 for y in y = x + 7

y = x + 7
-2x + 19 = x + 7

Subtract x from both sides

-2x + 19 - x = x + 7 - x

-3x + 19 = 7

Now subtract 19 on both sides

-3x + 19 - 19 = 7 - 19

-3x = -12

Then divide both sides by -3

-3x/-3 = -12/-3

x = 4

We have the value of x. Now we gonna use that same value to find the value for y.

We gonna do that by substitute 4 for x in y = -2x + 19

y = -2x + 19

y = -2(4) + 19

y = -8 + 19

y = 11

Thus,

The answer is: x = 4 and y = 11

Let me know if you have questions about the answer. As always, it is my pleasure to help students like you!

How can you use a random sample of a population to make predictions?

Answers

yes you can but you need to explain who and what your random sample is. and if you are making predictions it needs to be within the extrapolation of the data but thats collage level.

In scientific notation, what is the sum of 2.3 x 10^-3 and 5.4 x 10^-4

Answers

2,3\cdot 10^(-3)+5,4\cdot 10^(-4)=\n 2,3\cdot 10^(-3)+0,54\cdot 10^(-3)=2,84\cdot 10^(-3)

If you think that I helped You and this answer is the best, choose: The best answer and say thanks. Thanks! :)

Answer

5.68 x 10^5

Step-by-step explanation: